Studi Literatur : Bimbingan Kelompok Berbantuan Seni untuk Mereduksi Frekuensi Penggunaan Aplikasi Instagram pada Siswa - Barkafik Ali Hasan; Akhmad Fajar Prasetya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The rapid development of digital technology has increased the intensity of social media use among adolescents, particularly Instagram, leading to a decline in social interaction, low emotional regulation, and an increased tendency toward addictive behavior. Within the context of guidance and counseling, art possesses therapeutic potential, enabling students to express themselves and manage digital behaviors more adaptively. This study is a literature review analyzing seven selected scientific articles regarding the utilization of art in group counseling services. The analysis was conducted through data extraction of article characteristics, including research design, instruments, findings, and implications. The results indicate that art plays a significant role in supporting group dynamics, enhancing emotional regulation, and providing alternative activities capable of diverting students' attention from excessive Instagram use. Structured art activities also facilitate the development of self-awareness and self-control, thereby reducing the frequency of Instagram usage. These findings suggest that art-assisted group counseling is an effective and relevant strategy for guidance and counseling teachers to implement in addressing digital challenges within the school environment.